Differential Diagnosis of Rare Subtypes of Progressive Supranuclear Palsy and PSP-Like Syndromes—Infrequent Manifestations of the Most Common Form of Atypical Parkinsonism - Krzosek, Patrycja; Madetko, Natalia; Migda, Anna; Migda, Bartosz; Jaguś, Dominika; Alster, Piotr (Frontiers in Aging Neuroscience, 2022)
Growing interest is associated with recently more widely described variants of PSP other than PSP-RS and PSP-P. The exact diagnosis of these variants is extremely complex, as it is generally based on clinical manifestation. The accurate examination remains a major challenge for clinicians. Individual phenotypes often show high similarity not only to other neurodegenerative diseases but also to genetic, autoimmune or infectious disorders manifesting as PSP-mimicking syndromes. The limited data on rare PSP subtypes makes it impossible to isolate a specific technique that would give a chance for a confident ante-mortem diagnosis of each of the variants discussed. The aim of this review is to discuss recent developments concerning the assessment of the rare phenotypes of PSP and PSP-like syndromes.